2021
DOI: 10.1167/iovs.62.9.6
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Corneal TRPV1 and Its Association With Immune Cells During Homeostasis and Injury

Abstract: PURPOSE.Given the role of corneal sensory nerves during epithelial wound repair, we sought to examine the relationship between immune cells and polymodal nociceptors following corneal injury. METHODS.Young C57BL/6J mice received a 2 mm corneal epithelial injury. One week later, corneal wholemounts were immunostained using β-tubulin-488, TRPV1 (transient receptor potential ion channel subfamily V member-1, a nonselective cation channel) and immune cell (MHC-II, CD45 and CD68) antibodies. The sum length of TRPV1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 62 publications
0
25
0
Order By: Relevance
“…Conversely, TRPV1 expression is increased in models of extended lung pathology 165 167 leading to the conclusion that TRPV1 neurons can be both anti-inflammatory and pro-inflammatory, depending on the context. At the ocular surface, TRPV1 expression is upregulated after corneal injury 168 . Furthermore, activation of the nociceptive receptor, TRPV1, resulted in increased susceptibility to Pseudomonas aeruginosa infection 157 ; however, TRPV1 signaling also appears to appear to prevent the adhesion of environmental bacteria 169 .…”
Section: Neuroimmune Axis and The Modulation Of Mucosal Immunitymentioning
confidence: 99%
“…Conversely, TRPV1 expression is increased in models of extended lung pathology 165 167 leading to the conclusion that TRPV1 neurons can be both anti-inflammatory and pro-inflammatory, depending on the context. At the ocular surface, TRPV1 expression is upregulated after corneal injury 168 . Furthermore, activation of the nociceptive receptor, TRPV1, resulted in increased susceptibility to Pseudomonas aeruginosa infection 157 ; however, TRPV1 signaling also appears to appear to prevent the adhesion of environmental bacteria 169 .…”
Section: Neuroimmune Axis and The Modulation Of Mucosal Immunitymentioning
confidence: 99%
“…49 TRPV1 nerves were accounted for a higher proportion of corneal nerves at the ocular surface. 1,26 Despite its insensitivity to cold, TRPV1 has been shown to sensitize TRPM8 1 sensory neurons and promote neuropeptide substance P (SP) release to signal cold nociception. 29 TRPV4 is responsible for sensing hypoosmotic and mechanical signals.…”
Section: Introductionmentioning
confidence: 99%
“…TRPV1 is expressed in both neuronal and non-neuronal cells. It was shown that TRPV1+ nerves account for ~40% of nerve fiber length in the intact corneal epithelium and ~80% in the stroma and that following injury, TRPV1+ nerve density increases in a mouse model [ 28 ]. The activation of TRPV1+ nerves in the eye induces the release of neuropeptides such as neurokinins, calcitonin gene-related peptide (CGRP), and substance P (SP) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%